Differential electroencephalography responses in speech perception between native and non-native speakers - Quan, Luong Do Anh; Trang, Le Thi; Choi, Inyong; Woo, Jihwan (Frontiers in Human Neuroscience, 2025)
IntroductionNative and non-native listeners rely on different neural strategies when processing speech in their respective native and non-native languages, encoding distinct features of speech from acoustic to linguistic content in different ways. This study investigated differences in neural responses between native English and Korean speaker when they passively listened to speech in their native and non-native languages using electroencephalography.MethodsThe study employed two approaches to examine neural responses: Temporal Response Functions (TRFs) measure how the brain tracks continuous speech features (i.e., speech envelope, phoneme onset, phonemic surprisal, and semantic dissimilarity), and Phoneme-Related Potentials (PRPs) assess phonemic-level processes.ResultsNon-native speakers showed significantly stronger neural tracking of the speech envelope, but no group differences for higher-level linguistic features within analyses of TRFs. PRP analyses, however, revealed distinct response patterns across phoneme categories, with non-native speakers showing heightened peaks.ConclusionThe results suggest that non-native speakers rely more on bottom-up acoustic cues during passive listening. TRFs and PRPs provide information on neural markers that indicate how speech is processed differently depending on the listener's native language and language experience.